Editorial: Advances in artificial intelligence and robotics in joint arthroplasty - Andrew P. Kurmis; Sébastien Lustig; Francesco Zambianchi; Yunsu Chen (Arthroplasty)
Abstract The recently-completed special edition of Arthroplasty entitled 'Advances in Artificial Intelligence and Robotics in Joint Arthroplasty', brings together novel and innovative research from around the world in this cutting edge topic area. With robotics, artificial intelligence and technology-assistance (inside and out of the operating theatre) all becoming increasingly relevant to contemporary practice, we hope the readership will find this special edition an informative and thought-provoking read. Ultimately twelve individual papers were accepted for the edition, covering a range of exciting and novel applications. There clearly exists an ongoing need to provide further validation of new applications and, in many instances, replication of results away from designer sites is needed to provide robust generalizability of use. While several of the included papers show wide international collaboration, the prospect of future interactive work engaging leaders and think-tanks regionally and globally provides a tantalizing opportunity. With global health settings under increasing pressure and scrutiny to provide greater provision of joint replacement services – with the expectation of even more predictable (better) outcomes in a cost and resource efficacious manner – necessity will continue to drive further work exploring how technology-incorporation into arthroplasty care pathways might help address many of these considerations. There are undoubtedly exciting times ahead.